DESIGN AND IMPLEMENTATION OF IP EDUCATION IN THE PYTHON COURSE - Zhang, Ping; Wang, Jianzhong (IJRDO-Journal of Applied Science, 2023)
This article integrates the teaching content of Python programming course with Ideological and political (IP) education, and carries out the overall design of IP education In the Python course. Taking the turtle library, Jieba library, and Wordcloud library In the Python course as examples, a detailed design of IP education In the Python course is also carried out. Through the teaching design of IP education in this article, not only have the knowledge goals, ability goals, and emotional value goals of the python course been achieved, but also a way of thinking for other courses reforms and reference for other courses’ teachers to integrate IP concepts into their teaching.